Spin glass (2011)
Spin glass systems (SG) have been the subject of multiple investigations for more than four decades, known as complex systems behavior, due to the randomness in the arrangement of their spins, this behavior initially investigated in binary systems has been identified in more than 500 systems. Experimentally from measurements of magnetic susceptibility and electrical resistivity has been possible to identify this behavior, but over time have been included other characterization techniques. We present a brief overview of what has been the development of research in the SG that far from providing technical or detailed information, it seeks to give the reader an overview of what research has been SG experimentally so far.  Keywords: